REPRESENTASI KEKERASAN TERHADAP ANAK-ANAK DALAM FILM DESPICABLE ME - SARI, RINI PUSPITA (JURNAL KOMUNITAS, 2016)
Movie is one of the electronic media which is audio-visual. With movie we can convey a message that can influence the attitudes and perceptions. Moreover, easy access to get into film is able to entertain, educate, and inspire the audience. Two themes that generally cause anxiety and concern of the community is the scene that contains the elements of sexuality and violence. Concern and anxiety often stems from the belief that people who watch the film had the effect of moral issues, psychological, and cause antisocial behavior. Many cartoons which still contains scenes featuring violence, sensuality, and there are scenes that harm others. One example of a film that contains scenes of violence and interesting to be analyzed is Despicable Me, the genre of this movie is animation comedy crime. The aim of this study is to find out what forms of violence against children and how the meaning of violence against children depicted in the Despicable Me. This is a qualitative descriptive study. Source of data used in this study is a scene in the Despicable Me. The data in this study were all scenes involving violence against children. This study uses a two-stage analysis of semiotic Roland Barthes. The first step is to know the meaning of denotation analysis by looking at the scene and figures of speech that reflects the attitude of child abuse in every scene that has been classified as data and the determination of meaning in connotation as the second stepof the analysis done by seeing every scene figures that reflect the attitude of violence as social and cultural analysis. The results showed that the forms of violence against children who appear in the Despicable Me is physical violence, emotional abuse, neglect and child sexual abuse. In every scene contains various meanings, namely; (1) In the category of physical violence found in the fact that the majority of each scene contains elements threats to children, and (2) In the category of emotional abuse found in the fact that the majority of each scene contains elements of intimidation against children, (3) In the category of child neglect and sexual abuse found in the fact that the majority contain elements of each scene and do not care to child pornography and pornographic.Keyword : Semiotics, Film, Child abuse